Computational color imaging third international workshop, CCIW 2011, Milan, Italy, April 20-21, 2011. proceedings - Schettini, Raimondo; Tominaga, Shoji; Trémeau, Alain (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the Third Computational Color Imaging Workshop, CCIW 2010, held in Milan, Italy, in April 2010. The 16 revised full papers, presented together with three invited papers, were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on computational photography, color and perception, color imaging, and computational imaging.